2018
DOI: 10.1007/s40279-018-0927-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of Lower Limb Compression Garments During High-Intensity Exercise with Performance and Physiological Responses: A Systematic Review and Meta-analysis

Abstract: LLCGs were not associated with improved performance in VJ, VOmax, VOsubmax, [La], or RPE during high-intensity exercise. Such evidence should be taken into account when considering using LLCGs to enhance running performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 66 publications
0
27
0
Order By: Relevance
“…One of the main reasons for wearing CS during exercise is probably the expectation of performance enhancement due to potential physiological effects. 2 This includes better venous return which hasten metabolic removal from the exercising muscles 31 and reduce cardiac load, 26 improved proprioceptive feedback and better movement accuracy, 32 reduced muscle oscillations, lower muscle damage, inflammation, and soreness. 6,31 In the current review, only three studies found some CS-induced benefit on performance but did not present adirect mechanistic explanation.…”
Section: Cs and Performance Improvementmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main reasons for wearing CS during exercise is probably the expectation of performance enhancement due to potential physiological effects. 2 This includes better venous return which hasten metabolic removal from the exercising muscles 31 and reduce cardiac load, 26 improved proprioceptive feedback and better movement accuracy, 32 reduced muscle oscillations, lower muscle damage, inflammation, and soreness. 6,31 In the current review, only three studies found some CS-induced benefit on performance but did not present adirect mechanistic explanation.…”
Section: Cs and Performance Improvementmentioning
confidence: 99%
“…1 Over time, the interest from the basic medical area has expanded to other fields like Sports Medicine. 2 Nowadays, recreational and professional athletes have used CS as a tool for improving performance or accelerate recovery from training or competitions, and also to reduce lower limb volume, 3,4 relieve symptoms of muscle soreness, and fatigue. [3][4][5][6] Such popularity is probably boosted by the possibility to obtain potential ergogenic benefits with a simple and low-cost aid.…”
Section: Introductionmentioning
confidence: 99%
“…Inconsistent findings may be caused by heterogeneous conditions [55,57] and no consensus for optimal application time, applied pressure, composition as well as shape and design [57] could be provided thus far. Overall there is limited evidence to suggest that compression garments impact athletic performance [58,59,60], but there may be legitimation for its use in terms of recovery [55,57,61,62].…”
Section: Treatments and Strategies To Target Exercise-induced Muscmentioning
confidence: 99%
“…Multiple meta-analyses have investigated the effects of CGs on sports performance and post-exercise recovery [ 7 9 ]. Engel et al [ 7 ] found in their meta-analysis that using compression clothing, defined as knee-high socks, sleeves, or shorts, slightly improves running economy (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they reported that using compression sleeves or stockings slightly improves biomechanical variables (mean G= 0.21±0.38; range − 0.33 to 0.72), such as ground contact time, step frequency, step length and swing time, and the psychological variable perceived exertion (mean G= 0.28±0.38; range − 0.31 to 1.21) [ 7 ]. Whereas, the meta-analysis by Da Silva et al [ 9 ] found no effect of lower leg CGs on high-intensity exercise performance, defined as time difference in a maximum running test across specific distances (50–400 m, 800–3000 m, or > 5000 m), compared to no CGs or placebo garments. Regarding post-exercise recovery, two meta-analyses showed that using CGs decreases post-exercise leg soreness and delayed the onset of muscle fatigue and exercise induced-muscle damage respectively [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%